Coptischinensis Franch root rot infection disrupts microecological balance of rhizosphere soil and endophytic microbiomes - Tang, Tao; Wang, Fanfan; Fang, Guobin; Mao, Ting; Guo, Jie; Kuang, Hui; Sun, Guangzhong; Guo, Xiaoliang; Duan, Yuanyuan; You, Jingmao (Frontiers in Microbiology, 2023)
The ecological balance of the plant microbiome, as a barrier against pathogens, is very important for host health. Coptis chinensis is one of the important medicinal plants in China. In recent years, Illumina Miseq high-throughput sequencing technology was frequently used to analyze root rot pathogens and the effects of root rot on rhizosphere microorganisms of C. chinensis. but the effects of root rot infection on rhizosphere microecological balance of C. chinensis have received little attention. In this study, Illumina Miseq high-throughput sequencing technology was applied to analyze the impact on microbial composition and diversity of C. chinensis by root rot. The results showed that root rot infection had significant impact on bacterial α-diversity in rhizome samples, but had no significant effect on that in leaf samples and rhizosphere soil samples, while root rot infection exhibited significant impact on the fungal α-diversity in leaf samples and rhizosphere soil samples, and no significant impact on that in rhizome samples. PCoA analysis showed that the root rot infection had a greater impact on the fungal community structure in the rhizosphere soil, rhizome, and leaf samples of C. chinensis than on the bacterial community structure. Root rot infection destroyed the microecological balance of the original microbiomes in the rhizosphere soil, rhizome, and leaf samples of C. chinensis, which may also be one of the reasons for the serious root rot of C. chinensis. In conclusion, our findings suggested that root rot infection with C. chinensis disrupts microecological balance of rhizosphere soil and endophytic microbiomes. The results of this study can provide theoretical basis for the prevention and control of C. chinensis root rot by microecological regulation.